Strengthening Democracy through Campus: The Influence of Education on Student Political Participation - Sadeli, Elly Hasan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study investigates the impact of democratic education on student engagement in Indonesia’s 2024 General Elections. Using a quantitative survey design, data were collected from 250 students across five universities to examine their understanding of democratic concepts, perceptions of democratic education, and political participation. The findings indicate a moderate positive correlation (r = 0.412, p < 0.001) between democratic education and political engagement. While students exhibit strong foundational knowledge of democracy, their procedural understanding—such as knowledge of institutional mechanisms and electoral processes—remains limited. The study highlights the need for higher education institutions to adopt application-based approaches to democratic education, including electoral simulations, public debates, and advocacy training, to bridge the gap between theoretical knowledge and practical skills. By fostering informed and active political participation, such programs hold the potential to strengthen democratic resilience in Indonesia and other developing democracies. This research contributes to the global discourse on democratic education by providing empirical evidence from a developing country context. Future research should integrate qualitative methods and explore the role of social and institutional factors in shaping political engagement for a more comprehensive understanding of the dynamics between education and democracy.